Boungainvillea: An ideal ornamental plant for landscaping and pollution control - Meenu Kumari; Singh, Deepti; Singh, Paramveer; Sahay, Sanjay (Indian Horticulture, 2022)
Bougainvilleas have drawn interest of amateurs and garden plant lovers alike. High degree of variability and diverse uses has made them a plant of choice for landscape architects. It has also proven to be an ideal plant for green buildings and greening of wastelands, highways, etc. where landscaping needs to be promoted for minimizing different types of pollution and greening of extreme drought prone and marginal areas.